Intermittent Fasting Reshapes the Gut Microbiota and Metabolome and Reduces Weight Gain More Effectively Than Melatonin in Mice - Liu, Jingliang; Zhong, Yifan; Luo, Xin M.; Ma, Yanfei; Liu, Jianxin; Wang, Haifeng (Frontiers in Nutrition, 2021)
Background: Intermittent fasting (IF) can reduce energy intake and body weight (BW). Melatonin has many known functions, which include reducing appetite and preventing excessive weight gain. Objective: This study aimed to investigate the effects of IF on body fat and the gut microbiota and metabolome as well as a potential interaction with melatonin. Methods: Male C57BL/6J mice (23.0±0.9 g, 6 wk old) were randomly assigned into four groups (12 mice/group) in a 30-d 2 x 2 factorial design trial where they were either fed ad libitum (C) or underwent alternative-day feed deprivation (fasting, F), with or without melatonin supplementation (M, 10 mg/kg BW). Blood, epididymal fat, liver tissue, and intestinal tissue and contents were collected for lab measurements, histology, and microbiota and metabolome analysis. Main effects and interactions were tested by 2-factor ANOVA. Results: Fasting significantly reduced BW gain and serum glucose, total cholesterol (TC) and triglyceride (TG) levels. Adipocyte size significantly decreased with IF, but the number of adipocytes increased (P<0.05). Compared to the C group, the M and MF groups had significantly higher serum melatonin levels (17% and 21%, respectively), although melatonin monotherapy had no effect on serum parameters and adipocytes. There was no interaction between IF and melatonin on BW gain and serum parameters except for on adipocyte area and number, Bacteroidetes and Akkermansia bacterial abundance, and the levels of the intestinal metabolites alanine, valine and isoleucine. IF changed the intestinal microbiota structure, with the F and MF groups clearly separated from the C and M groups. Metabolomic analysis showed that there was obvious separation between all 4 groups. Conclusions: IF, but neither melatonin nor the interaction between IF and melatonin, could alter intestinal microbiota and metabolism and prevent obesity by reducing BW gain, serum glucose, TC, and TG, and adipocyte size in mice.